Pathogenesis of Hepatic Encephalopathy - Irena Ciećko-Michalska; Małgorzata Szczepanek; Agnieszka Słowik; Tomasz Mach (Gastroenterology Research and Practice)
Hepatic encephalopathy can be a serious complication of acute liver failure and chronic liver diseases, predominantly liver cirrhosis. Hyperammonemia plays the most important role in the pathogenesis of hepatic encephalopathy. The brain-blood barrier disturbances, changes in neurotransmission, neuroinflammation, oxidative stress, GABA-ergic or benzodiazepine pathway abnormalities, manganese neurotoxicity, brain energetic disturbances, and brain blood flow abnormalities are considered to be involved in the development of hepatic encephalopathy. The influence of small intestine bacterial overgrowth (SIBO) on the induction of minimal hepatic encephalopathy is recently emphasized. The aim of this paper is to present the current views on the pathogenesis of hepatic encephalopathy.